The impact of community-based tourism development on the socio-economic dimensions of local communities in the coastal area of Ambon Island - Mony, Farida; Azuz, Fidaan; Zakaria, Syawal; Marasabessy, Achmad; Kaisupy, Tina (Technium Social Sciences Journal, 2023)
Sustainable and well-developed tourism requires the participation of the community both as managers and as supporters of private industry. The existence of local communities in tourism activities is known as community-based tourism (CBT) which requires synergy between the government, local communities, and tourism industry stakeholders. This study aims to identify the tourism potential that can be developed into CBT, analyse the impact of the presence of CBT on socio-economic activities, and analyse the supporting and inhibiting factors for the development of CBT on the people surrounding the beach of Ambon Island. The results show that there are still several places that can be developed into CBT spots that located in districts of Leihitu, South Leitimur, Salahutu, Nusaniwe, and West Leihitu. Managed CBT still has the opportunity to improve facilities and various types of tourism products, especially those related to maritime affairs. The presence of CBT in the coastal area of Ambon Island has positive impacts on the community, new mindsets, behavior and business motivation, as well as increasing community creativity in economic business, especially culinary businesses, lodging, transportation services, and other tourism supporting products.